The effect of multimedia stories about American deaf celebrities on Taiwanese hearing students' attitudes toward job opportunities for the deaf. - Ju J (American Annals of the Deaf)
In Taiwan, hearing people generally think deaf individuals can only do jobs requiring minimal communication. The present study was planned to help change hearing people's attitudes toward deaf people's job competence. Multimedia stories of deaf celebrities, e.g., physicians, lawyers, university presidents, professors, senior government officials, and movie stars, were developed. A multimedia computer reading program was developed in which graphic organizers, picture clues, video, and voice were integrated to make reading more exciting and pleasant. Materials were developed to be suitable for dissemination on CD. Regarding attitude change, all differences between pretests and posttests were statistically significant: Hearing student's attitudes toward deaf and hard of hearing people changed positively and significantly. It is recommended that the CD featuring American deaf celebrities be distributed to make hearing people understand deaf people's potential, and to contribute to an environment conducive to their employment in Taiwan.